DPPC Bilayers in Solutions of High Sucrose Content - Morandi, Mattia I. (Biophys J, 2018)
The properties of lipid bilayers in sucrose solutions have been intensely scrutinized over recent decades because of the importance of sugars in the field of biopreservation. However, a consensus has not yet been formed on the mechanisms of sugar-lipid interaction. Here, we present a study on the effect of sucrose on 1,2-dipalmitoyl-sn-glycero-3-phosphocholine bilayers that combines calorimetry, spectral fluorimetry, and optical microscopy. Intriguingly, our results show a significant decrease in the transition enthalpy but only a minor shift in the transition temperature. Our observations can be quantitatively accounted for by a thermodynamic model that assumes partial delayed melting induced by sucrose adsorption at the membrane interface.